Guy Ritchie's The covenant [videorecording (DVD)] - Ritchie, Guy; Atkinson, Ivan; Davies, Marn; Gyllenhaal, Jake, 1980-; Salim, Dar, 1977-; Starr, Antony, 1975-; Ludwig, Alexander, 1992-; Sagar, Sean; Schofield, Bobby, 1993-; Beecham, Emily, 1984-; Miller, Jonny Lee (Warner Bros Entertainment Inc., 2023)
Guy Ritchie's The Covenant follows US Army Sergeant John Kinley (Jake Gyllenhaal) and Afghan interpreter Ahmed (Dar Salim). After an ambush, Ahmed goes to Herculean lengths to save Kinley's life. When Kinley learns that Ahmed and his family were not given safe passage to America as promised, he must repay his debt by returning to the war zone to retrieve them before the Taliban hunts them down first.